The Influence of Sales Promotion on Consumer Buying Behaviour in the Telecom Industry; the Case of Vodafone Ghana. - Darko, Eric (2013)
A Thesis submitted to the Institute of Distance Learning, Kwame Nkrumah University of Science and Technology, Kumasi in partial fulfillment of the requirements for the degree of Commonwealth Executive Masters of Business Administration